2016
DOI: 10.5851/kosfa.2016.36.6.799
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Sensory Characteristics of Reduced-fat Chicken Patties with Pork Back Fat Replaced by Dietary Fiber from Wheat Sprout

Abstract: The effects of reducing pork fat levels from 20% to 15% or 10% by partially substituting pork back fat with wheat sprout fiber in reduced-fat chicken patties were investigated. Approximate composition, energy value, pH, color, cooking loss, reduction in diameter, reduction in thickness, shear force, and sensory properties were determined. Moisture content, ash contents, yellowness of uncooked and cooked reduced-fat chicken patties with wheat sprout were higher than those in the control, while displaying fat co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Kim et al () reported lower cooking loss of chicken nugget formulated with pre‐emulsion of chicken skin and wheat fiber mixture as compared with the control. These results are consistent with those of Choi et al (), wherein the reduction in the diameter and thickness was lower upon increase in the fat content and wheat sprout levels. The results of the reduction in the diameter and thickness of reduced‐fat chicken patties were similar to those of cooking loss.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Kim et al () reported lower cooking loss of chicken nugget formulated with pre‐emulsion of chicken skin and wheat fiber mixture as compared with the control. These results are consistent with those of Choi et al (), wherein the reduction in the diameter and thickness was lower upon increase in the fat content and wheat sprout levels. The results of the reduction in the diameter and thickness of reduced‐fat chicken patties were similar to those of cooking loss.…”
Section: Resultssupporting
confidence: 93%
“…The yellowness of the reduced‐fat chicken patties with pre‐emulsion was higher than that of the control ( p < .05), and the yellowness of the reduced‐fat chicken patties increased significantly with an increase in the pre‐emulsion level ( p < .05). Choi et al () reported a decrease in the lightness and redness value of uncooked and cooked low‐fat chicken patties with an increase in the wheat sprout levels. In addition, Lee et al () reported that the addition of wheat sprout and isolated soy protein affected the color attributes of breakfast sausages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both pH and Aw (6.3±0.1 vs. 0.8±0.02) values of grilled samples with added chia seeds also placed similar for control. It was expected that increased chia seeds added could cause an increase in Aw and decreasing of pH (CHOI et al, 2016). A explanation of the results reported this experiment could be related to the fact that there were no differences in protein and moisture of raw samples, and, the addition of chia seeds have provided a small variation in carbohydrates content and greater reduction of fat content due to the increased amounts of chia seeds.…”
Section: Resultsmentioning
confidence: 64%